Recovering Identity Criminalized Women's Fight for Dignity and Freedom - Rumpf, Cesraéa (University of California Press, 2023)
Recovering Identity examines a critical tension in criminalized women's identity work. Through in-depth qualitative and photo-elicitation interviews, Cesraéa Rumpf shows how formerly incarcerated women engaged recovery and faith-based discourses to craft rehabilitated identities, defined in opposition to past identities as "criminal-addicts." While these discourses made it possible for women to carve out spaces of personal protection, growth, and joy, they also promoted individualistic understandings of criminalization and the violence and dehumanization that followed. Honoring criminalized women's stories of personal transformation, Rumpf nevertheless strongly critiques institutions' promotion of narratives that impose lifelong moral judgment while detracting attention from the structural forces of racism, sexism, and poverty that contribute to women's vulnerability to violence. "A deeply moving account of the indignity that women who are criminalized experience as they fight for their freedom. Cesraéa Rumpf's sharp critique demands that we see the violence of incarceration and deepen our commitment to justice for criminalized women." - BETH E. RICHIE , coauthor of Abolition. Feminism. Now. "Recovering Identity makes a major contribution to the study of gender, race, and culture in the era of mass incarceration. Rumpf's comprehensive analysis of how women counter the negative effects of the criminal legal system is timely, thoroughly researched, and persuasive." - KEESHA M. MIDDLEMASS, author of Convicted and Condemned: The Politics and Policies of Prisoner Reentry "Rumpf persuasively demonstrates how 12-step ideology obscures the structural forces driving mass incarceration. A sensitive, rigorous, and compelling contribution." - MELISSA THOMPSON, coauthor of Motherhood after Incarceration: Community Reintegration for Mothers in the Criminal Legal System